CXCL12 is required for stirrup‐shaped stapes formation during mammalian middle ear development. Issue 9 (2nd May 2020) - Ankamreddy, Harinarayana; Koo, Heiyeun; Lee, Young Jae; Bok, Jinwoong
Abstract: Background: The mammalian middle ear comprises a chain of three ossicles—the malleus, incus, and stapes—each of which has a unique morphology for efficiently transmitting sound information. In particular, the stapes, which is attached to the inner ear, is stirrup‐shaped with a head and base connected by two crural arches, forming the stapedial foramen, through which the stapedial artery passes. However, how the stapes acquires this critical stirrup shape for association with the stapedial artery during development is not clear. Results: C‐X‐C motif chemokine ligand 12 (CXCL12) is a chemoattractant essential for cellular movement and angiogenesis. In Cxcl12 −/− embryos, migration of neural crest cells into the prospective middle ear regions and their mesenchymal condensation to form the three ossicles proceed normally in correct alignment with each other and the inner ear. However, in the absence of CXCL12, the stapes loses its stirrup shape and instead exhibits a columnar shape lacking the crural arches and central hole. In addition, although the stapedial artery initially forms during early mesenchymal condensation of the stapes, it degenerates without CXCL12 function. Conclusion: CXCL12 plays an essential role in establishing the stirrup‐shaped architecture of the stapes, possibly by maintaining the stapedial foramen and stapedial artery throughout development. Key Findings: The stapes is a stirrup‐shaped ossicle with a central foramen through which the stapedial artery penetrates. Cxcl12 is expressed in the condensing mesenchyme that forms the stapedial anlagen. The stapedial artery and stapedial foramen fail to form in the absence of CXCL12. CXCL12 is required for establishing the stirrup shape during stapes development.